2020
DOI: 10.22219/jrak.v10i3.13273
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intellectual Capital Performance on Company's Financial Performance

Abstract: This study analyzes the effect of intellectual capital performance on the company's financial performance in the current year and the following year. We use the Modified Value Added Coefficient (MVAIC) to measure the performance of company's intellectual capital. The research sample is companies listed on the Indonesia Stock Exchange (BEI) 2015-2017 which are included in the High-IC intensive industries category based on the classification of the Global Industries Classification Standard (GICS). Samples were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Structural capital owned by the company has fulfilled the routine processes and company structure so as to support the efforts of employees in producing optimal intellectual performance and overall business performance. Pramathana and Widarjo (2020) also show that intellectual capital has a positive effect on the company's financial performance, meaning that the higher the company's intellectual capital performance, the higher the company's financial performance will be. Structural Capital (SC) and Capital Employed (CE) have the strongest influence on the company's financial performance in the current period.…”
Section: Effect Of Structural Capital (Hc) On Financial Performance (...mentioning
confidence: 91%
“…Structural capital owned by the company has fulfilled the routine processes and company structure so as to support the efforts of employees in producing optimal intellectual performance and overall business performance. Pramathana and Widarjo (2020) also show that intellectual capital has a positive effect on the company's financial performance, meaning that the higher the company's intellectual capital performance, the higher the company's financial performance will be. Structural Capital (SC) and Capital Employed (CE) have the strongest influence on the company's financial performance in the current period.…”
Section: Effect Of Structural Capital (Hc) On Financial Performance (...mentioning
confidence: 91%
“…Oleh karena itu, mengukur profitabilitas perusahaan sangatlah penting dalam hubungan pemilik investor (Putra & Gantino, 2021). Hal ini sesuai dengan teori sinyal bahwa modal intelektual perusahaan harus dipandang sebagai sinyal baik pada investor, karena nilai aset tersebut mencerminkan nilai modal intelektual industri (Pramathana & Widarjo, 2020). Teori Keagenan (Agency Theory)…”
Section: Kajian Teoritis Teori Sinyal (Signalling Theory)unclassified
“…ey found that physical and human capitals positively impact operating profit and net income, while SC has a negative impact. Pramathana and Widarjo [42], using the MVAIC model, measured IC performance of Indonesia firms and found that the impact of physical capital, HC, and SC is positive, while the impact of RC is negative. In a study on Chinese manufacturing sector, Xu and Liu [43] reported a high significant correlation of IC with corporate profitability and return.…”
Section: Ic Definition and Measurement Many Researchers Havementioning
confidence: 99%